OHP-043 The pharmacist "monitor" at the E. R.: the experience of "Gaetano Rummo" hospital of Benevento. (24th February 2014) - Ruggiero, F; Taurasi, F; Melillo, A; Russo, L
Abstract : Background: The Emergency Room (ER) represents a strategic location for pharmacovigilance due to easy access, permanent availability and a multidisciplinary clinical approach. Purpose: To investigate over a period of twenty-four months how much a constant pharmacist presence in the ER could encourage ER personnel to report ADEs promptly, encouraging greater attention to be paid to their clinical relevance. Materials and methods: Monitoring done by the pharmacist in the ER of Gaetano Rummo Hospital (BN), allowed the collection of medical, diagnostic and clinic data regarding suspicious ADEs and patients involved. The information is collected and transcribed in the form provided by AIFA (the Italian Medicines Agency), evaluated and entered into the National Pharmacovigilance Network. The pharmacist also provided monthly reports which described the number of ADEs reported, a description of the ADEs and suspicious medicines. Results: In the two years of monitoring, the following data has been collected: in total 253 reports (3 paediatric cases, 123 adults and 127 over 65) with a slightly majority of male patients (128). Of these, 42.7% were regarded as 'Serious' (4 lives endangered, 103 required hospitalisation or prolonged hospitalisation and one resulted in death). Of the iatrogenic pathologies highlighted 71.6% involved skin and subcutaneous tissue rash (96), gastrointestinal reactions (82), systemic disorders and conditions related to the administration site (53), respiratory, thoracic and mediastinal disorders (50) and, finally, diseases of the nervous system (44). The suspicious drugs were mainly ASA and warfarin (24). Conclusions: From the results obtained, extensive monitoring of medicines represents an important cost-saving opportunity related to the appearance of ADEs and a crucial source of reports on pharmacokinetic/pharmacodynamic problems of medicinal products on the market. This leads to an improvement in the quality of health care. No conflict of interest.